El viaje del argentino César Vásquez a los Estados Unidos del Brasil (1941): entre internacionalizar y hacer una Educación Física nacional - Galak, Eduardo Lautaro (2024)
Abstract:The General Directorate of Physical Education (“Dirección General de Educación Física”), a branch of the Ministry of Justice and Public Instruction of Argentina, operated from 1938 to 1947, marking a significant era in the discipline within the country. Its sole director, César Vásquez, stands as a prominent figure in the history of Argentine Physical Education. This article aims to analyze Vásquez's 1941 trip to Brazil, which was positioned within a Pan-American context that coexisted with nationalist narratives. This journey initiated a series of exchanges between the Physical Education authorities of both countries, revealing the image they intended to project to their neighbor. The sources utilized include detailed newspaper articles covering the trip and bulletins from the aforementioned Ministry, which contextualize these exchanges. The analysis concludes that the institutionalization of Argentine Physical Education exhibited a strong connection with both national and international organizations. Vásquez's trip marked a transnational opening, shaping the discipline in contrast to practices in other countries and challenging the exclusive European dominance within the framework of Pan-Americanism. Additionally, it is noted that the aspects showcased to Brazil, although presented as representative of all Argentina, predominantly highlighted developments in the Federal Capital and its surroundings. This underscores that the federalizing discourse of the General Directorate was primarily centered on the major cities.